Regulation of the orexigenic neuropeptide, enkephalin, by PPARδ and fatty acids in neurons of the hypothalamus and forebrain. (29th September 2015) - Poon, Kinning; Alam, Mohammad; Karatayev, Olga; Barson, Jessica R.; Leibowitz, Sarah F.
Abstract: Ingestion of a high‐fat diet composed mainly of the saturated fatty acid, palmitic (PA), and the unsaturated fatty acid, oleic (OA), stimulates transcription in the brain of the opioid neuropeptide, enkephalin (ENK), which promotes intake of substances of abuse. To understand possible underlying mechanisms, this study examined the nuclear receptors, peroxisome proliferator‐activated receptors (PPARs), and tested in hypothalamic and forebrain neurons from rat embryos whether PPARs regulate endogenous ENK and the fatty acids themselves affect these PPARs and ENK. The first set of experiments demonstrated that knocking down PPARδ, but not PPARα or PPARγ, increased ENK transcription, activation of PPARδ by an agonist decreased ENK levels, and PPARδ neurons coexpressed ENK, suggesting that PPARδ negatively regulates ENK. In the second set of experiments, PA treatment of hypothalamic and forebrain neurons had no effect on PPARδ protein while stimulating ENK mRNA and protein, whereas OA increased both mRNA and protein levels of PPARδ in forebrain neurons while having no effect on ENK mRNA and increasing ENK levels. These findings show that PA has a strong, stimulatory effect on ENK and weak effect on PPARδ protein, whereas OA has a strong stimulatory effect on PPARδ and weak effect on ENK, consistent with the inhibitory effect of PPARδ on ENK. They suggest a function for PPARδ, perhaps protective in nature, in embryonic neurons exposed to fatty acids from a fat‐rich diet and provide evidence for a mechanism contributing to differential effects of saturated and monounsaturated fatty acids on neurochemical systems involved in consummatory behavior. Our findings show that PPARδ in forebrain and hypothalamic neurons negatively regulates enkephalin (ENK), a peptide known to promote ingestive behavior. This inverse relationship is consistent with our additional findings, that a saturated (palmitic; PA) compared to a monounsaturated fatty acid (oleic; OA) has a strong stimulatory effect on ENK and weak effect on PPARδ. These results suggest that PPARδ protects against the neuronal effects of fatty acids, which differentially affect neurochemical systems involved in ingestive behavior. Abstract : Our findings show that PPARδ in forebrain and hypothalamic neurons negatively regulates enkephalin (ENK), a peptide known to promote ingestive behavior. This inverse relationship is consistent with our additional findings, that a saturated (palmitic; PA) compared to a monounsaturated fatty acid (oleic; OA) has a strong stimulatory effect on ENK and weak effect on PPARδ. These results suggest that PPARδ protects against the neuronal effects of fatty acids, which differentially affect neurochemical systems involved in ingestive behavior.